Usability of a memory aid handbook for older people with subjective cognitive impairment—An explorative pilot study - Ross, Sabrina D.; Rodriguez, Francisca S. (International journal of geriatric psychiatry, 2023)
Background Memory problems are common in advanced age. Memory strategies can be used to manage such challenges. To assist older people facing memory problems, we conducted a pilot study to evaluate the usability of a memory aid handbook that we developed specifically for this purpose. Method A memory aid handbook with a 7‐week program was developed based on a systematic review. A total of 19 older people with self‐reported memory problems (mean age: 76.11 years, female: 73.68%) tested the memory aid handbook and completed the System Usability Scale (SUS), a checklist on the relevance of the strategies in the handbook, and questionnaires on daily life functioning and self‐efficacy. Further, they participated in cognitive tests. In a pre‐post design, within‐subject differences were determined using paired t‐tests. Results The usability of the memory aid handbook scores as were high (mean SUS score: 99.21). The checklist indicated that the handbook was perceived as beneficial for confirming already established memory strategies and stimulating new ones, such as self‐acceptance, visualizing and verbalizing daily routines, and asking for help. In addition, the checklist revealed that using a calendar was considered the most helpful strategies for daily living, followed closely by taking notes, having specific places for certain items and creating routines in daily life. After the 7 weeks, participants scored significantly better in the cognitive and self‐efficacy tests. The exploratory nature of the study combined with the small sample size should be considered when interpreting the results. Conclusion The usability of the handbook was high, reflecting the relevance of the strategies it contains. Teaching memory strategies can be a useful, inexpensive method to foster independence among those at risk for cognitive impairment. Key points People with memory problems perceived a memory aid handbook as useful in confirming already established memory strategies and stimulating new ones or revising old ones. Using a calendar was considered the most helpful strategy for daily living, followed closely by taking notes, staying organized, having specific places for specific things, creating routines in daily life, and avoiding time pressure. New incentives provided by the memory aid handbook included self‐acceptance, visualizing and verbalizing daily routines, and asking for help and encouraging older people with memory problems to rethink old such as putting frequently used items in a more prominent place. The memory aid handbook received the best imaginable usability score, and is characterized by great ease of use, rendering it suitable for independent use by elderly individuals with subjective cognitive impairment.